Using offsets to mitigate environmental impacts of major projects: A stakeholder analysis. (1st September 2016) - Martin, Nigel; Evans, Megan; Rice, John; Lodhia, Sumit; Gibbons, Philip
Abstract: Global patterns of development suggest that as more projects are initiated, business will need to find acceptable measures to conserve biodiversity. The application of environmental offsets allows firms to combine their economic interests with the environment and society. This article presents the results of a multi-stakeholder analysis related to the design of offsets principles, policies, and regulatory processes, using a large infrastructure projects context. The results indicate that business was primarily interested in using direct offsets and other compensatory measures, known internationally as indirect offsets, to acquit their environmental management obligations. In contrast, the environmental sector argued that highly principled and scientifically robust offsets programs should be implemented and maintained for enduring environmental protection. Stakeholder consensus stressed the importance of offsets registers with commensurate monitoring and enforcement. Our findings provide instructive insights into the countervailing views of offsets policy stakeholders. Graphical abstract: Highlights: Global growth above 3.5% through 2016 suggests more large-scale development projects. The study's five headline projects cover 31, 500 ha cleared land and 75, 500 ha offsets. Firms sought to use direct and indirect offsets to acquit environmental obligations. Environmental advocates argued for robust enforcement of offsets programs. Offsets registers are critically important environment information management tools.